A Multiple Case Study on Parents' Perspective about the Inftuence of the Islamic Culture on Muslim Children's Daily Lives - Shalabi, Dina (University of Ottawa (Canada), 2010)
In a multicultural society, there should be a pressing need to acknowledge the cultural heritages and social variations of its members in order to validate their experiences and realities. The purpose of this multiple case study was to explore how Muslim parents interpreted the influence of the Islamic culture on their children's daily lives. The study addressed this influence by examining Muslim children's daily funds of knowledge. This study also aimed to examine how Muslim parents suggested their children's fund of knowledge to be addressed in a culturally responsive pedagogical model at public schools. Muslim parents in five ethnically diverse households were interviewed, and observational notes about physical surrounding during the interview sessions were recorded. A qualitative multiple case study was designed to answer research questions and understand the influence of the Islamic culture in these households. Data was analyzed through the integration of the analysis framework adapted from Stake (2006) while using Nvivo computer software for analyzing qualitative data. Eight themes emerged from the study and allowed for a discussion on the centrality of the religion in these households, the collective cultural paradigm, and the scope of identity negotiation taking place on a daily basis. For the purpose of this study, implications to educators were incorporated into Gay's (2000) characteristics of cultural responsive teaching in order to integrate Muslim students into classroom pedagogies.
Keywords: Education, Multilingual.; Islamic Studies.